Analysis of the real exchange rate misalignment in Honduras - CASCO ALFARO, Elvis Teodoro (KDI School, 2015)
In this document is discussed the real exchange rate misalignment for Honduras and the consequences of the adjustment to nominal exchange rate in inflation. Results show that the depreciation of the nominal exchange rate resulted in a very low appreciation of the real exchange rate during the last two years (less than 2%). A higher nominal exchange rate depreciation has a negative impact on inflation considering two price channels: 1) the increasing of the price of imported goods (elasticity to inflation equal to 0.059), and 2) the higher oil derivatives prices affecting food prices (elasticity to food prices of 0.208) and the total inflation rate, with elasticity of oil derivatives to inflation equal to 0.362 and elasticity of food to inflation of 0.352. Giving this situation, the actual adjustment in the nominal exchange rate applied until now is close to the equilibrium values of its fundamentals. However, it is convenient to continue observing the behavior of these variables, considering the application of monetary policy adjustments in case of a high misalignment in the future. This document uses the Error Correction Model to estimate the real exchange misalignment, and Structural Vector Autoregression methodology to evaluate the impact of prices on inflation.
Thesis(Master) --KDI School:Master of Development Policy,2015